Comparative Seismic Analysis of G+20 RC Framed Structure Building for with and without Shear Walls - Rohit Maheshwari (Journal of the Civil Engineering Forum, 2024)
The performance of High-rise Reinforced Concrete (R.C.) design buildings with the shear wall is targeted to provide stability, simplicity of maintenance, and durability of the framed structure. The impacts of lateral loads, axial forces, shear forces, base shear, maximum story drift, and tensile forces are common in high-rise structural systems. The present paper analyses G+20 story R.C. framed buildings for base shear, maximum story displacement and bending moment behaviour of structures with and without shear walls under seismic loading. The building is located in Dehradun, and the load has been considered as per I.S. code 1893:2016. Framed has been analysed using E-tabs to identify maximum base shear for the concern load conditions. The result shows that the frame designed with an appropriate shear wall absorbs more lateral forces, and minimum displacement values are induced and resist maximum moments throughout the height of the building when a structure is appropriately configured with a shear wall. The structure configured with the shear walls has high resistance to absorb earthquake forces compared to structures without shear walls.